2008
DOI: 10.1542/peds.2007-1218
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Intravenous Immunoglobulin in the Treatment of Juvenile Dermatomyositis: Adverse Reactions Are Associated With Immunoglobulin A Content

Abstract: Intravenous immunoglobulin was found to be safe and well tolerated by most children with juvenile dermatomyositis. However, in contrast to adult studies, we found that significant differences existed in tolerance to different intravenous immunoglobulin products, most likely because of immunoglobulin A concentration. This study confirms anecdotal reports that a high level of immunoglobulin A in intravenous immunoglobulin is less well tolerated by children and provides evidence that product choice is important i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 17 publications
1
23
1
Order By: Relevance
“…The safety of IVIG was confirmed in 38 JDM patients receiving 1,056 infusions, with the most common complaints being fever, malaise, nausea, and vomiting [12]. A distinct advantage of IVIG therapy is the ability to use it as addon therapy or in combination, even in the setting of infection.…”
Section: Intravenous Immunoglobulinmentioning
confidence: 92%
“…The safety of IVIG was confirmed in 38 JDM patients receiving 1,056 infusions, with the most common complaints being fever, malaise, nausea, and vomiting [12]. A distinct advantage of IVIG therapy is the ability to use it as addon therapy or in combination, even in the setting of infection.…”
Section: Intravenous Immunoglobulinmentioning
confidence: 92%
“…39 A retrospective review of pediatric patients treated with different IGIV products found that significantly fewer adverse events were associated with IGIV products containing lower levels of IgA. 40 Hyperosmolar IGIV solutions may be associated with hemodynamic changes and an increased risk for infusion-related adverse events, especially thromboembolic stroke. 11,17,41 One study found a 0.6% rate of stroke among patients receiving IGIV at their medical center.…”
Section: Similarities and Differences In Igiv Productsmentioning
confidence: 99%
“…Manlhiot et al [26] compared the incidence of adverse events with juvenile dermatomyositis. Among the 38 patients at a median age of 10 years, Gammagard S/D was associated with the lowest frequency of adverse events compared with 3 other products.…”
Section: Specific Ivig Productsmentioning
confidence: 99%
“…The most common reactions included fever, headache, nausea/vomiting, and lethargy. No life-threatening reactions occurred [26]. …”
Section: Specific Ivig Productsmentioning
confidence: 99%
See 1 more Smart Citation